2016
DOI: 10.1186/s12955-016-0562-z
|View full text |Cite
|
Sign up to set email alerts
|

Exercise stereotypes and health-related outcomes in French people living with HIV: development and validation of an HIV Exercise Stereotypes Scale (HIVESS)

Abstract: BackgroundThe main objective of the current study was to develop and validate a French exercise stereotype scale for people living with HIV (PLHIV) in order to gain visibility to the possible barriers and facilitators for exercise in PLHIV and thus enhance their quality of life.MethodsA series of four complementary studies was carried out with a total sample of 524 participants to: (a) develop a preliminary version of the HIV Exercise Stereotype Scale (HIVESS) (Stage 1), (b) confirm the factorial structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We used the HIV Exercise Stereotype Scale (HIVESS) developed and validated by Gray et al [ 9 ] to assess endorsement of exercise stereotypes in PLHIV. The HIVESS consists of 14 items divided into three subscales: (a) five items measured stereotypes related to exercise benefits for PLHIV (e.g., “Physical activity improves the morale of HIV-infected patients”), (b) four items measured stereotypes related to exercise risks linked to injury (e.g., “Practicing a physical activity should be avoided by HIV-infected patients because it causes injuries”) and linked to contamination (e.g., “HIV-infected patients do not practice physical activities because they could contaminate someone during the activity”) and (c) five items measured stereotypes related to a lack of capacity of PLHIV for exercise (e.g., “HIV-infected patients do not have enough physical resources to practice a physical activity”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the HIV Exercise Stereotype Scale (HIVESS) developed and validated by Gray et al [ 9 ] to assess endorsement of exercise stereotypes in PLHIV. The HIVESS consists of 14 items divided into three subscales: (a) five items measured stereotypes related to exercise benefits for PLHIV (e.g., “Physical activity improves the morale of HIV-infected patients”), (b) four items measured stereotypes related to exercise risks linked to injury (e.g., “Practicing a physical activity should be avoided by HIV-infected patients because it causes injuries”) and linked to contamination (e.g., “HIV-infected patients do not practice physical activities because they could contaminate someone during the activity”) and (c) five items measured stereotypes related to a lack of capacity of PLHIV for exercise (e.g., “HIV-infected patients do not have enough physical resources to practice a physical activity”).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Wurm, Tomasik, and Tesch-Romer [ 7 ] showed that positive views of aging contributed to a higher level of PA. Besides age stereotypes, exercise stereotypes have been identified in recent literature, as playing a major role in the relation to PA [ 8 , 9 ]. These exercise stereotypes, which different populations endorse, or adhere to, to varying degrees, can be both positive and negative and have been the source of specific exercise stereotype scales being developed for the elderly [ 10 ], cancer patients [ 8 ], and more recently for people affected by HIV/AIDS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists the characteristics of the included PROMs, with details of the subscales provided in Table S3 in Multimedia Appendix 1. A total of 88 PROMs were reported in the 152 included studies, and these PROMs can be divided into 8 categories (improved based on the initial taxonomy developed by Engler et al [22]): HRQoL (24/88, 27% of PROMs) , symptoms (10/88, 11% of PROMs) [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], stigma (15/88, 17% of PROMs) , psychological (8/88, 9% of PROMs) [143][144][145][146][147][148][149][150][151], body and facial appearance (5/88, 6% of PROMs) [152][153][154][155][156], treatment (17/88, 19% of PROMs) , social support (3/88, 3% of PROMs) [174][175][176], and self-management and self-care (6/88, 7% of PROMs) [177][178][179][180][181][182]. All the included PROMs were tools self-administered by people livi...…”
Section: Characteristics Of the Included Promsmentioning
confidence: 99%
“…• Class C: The PROMs with high-quality evidence for an "insufficient" psychometric property included the following: Multidimensional Quality of Life for patients With HIV and AIDS [72][73][74][75], Patient-Reported Outcome Quality of Life-HIV Questionnaire-38 [101], HIV-Related Fatigue Scale [113][114][115], HIV Stigma Scale-10 [130], HIV or AIDS Stress Scale [144], Screenphiv [146,147], SECope [167], and HIV Exercise Stereotypes Scale [181]. They may not be recommended for use.…”
Section: Recommendationsmentioning
confidence: 99%
“…Exploring their attitudes, and understanding their thoughts about physical activity and exercise, will also assist in distinguishing between the viewpoints of participants with, and without, established exercise habits. The identification of the influences on exercising or routine physical activity, such as physical health and self-efficacy, and accessibility to safe environments for exercise, is also an imperative [ 21 ]. It is important to identify the facilitators of, barriers to and suitable environments for physical activity and exercise, specific to older adults living with HIV taking context into consideration.…”
Section: Introductionmentioning
confidence: 99%